Students’ Grammatical Error Analysis In Writing Composition At 11TH Grade Of MA AL-FALAH Pamekasan - Ina Daril Hanna Ina Daril Hanna; Khairiyatur Romdlanah (Universitas Islam Lamongan, 2026)
This study investigates grammatical errors in writing daily composition texts among eleventh-grade students at MA Al-Falah. The research addresses two main questions: the types of grammatical errors that occur in students’ compositions on daily activities and the most dominant type of error. Grammatical accuracy is an essential aspect of writing proficiency, yet many students struggle to produce error-free compositions. A qualitative research design was employed, with 26 students as respondents. Data were collected through documentation of students’ written works and analyzed to identify error types based on a linguistic error taxonomy. The findings reveal four types of errors: omission, addition, misformation, and misordering. Omission errors were the most frequent, occurring in 61,76% of cases, followed by addition at 38,24%, while misformation and misordering did not appear in the data. These outcomes underscore the critical necessity for strategically structured pedagogical interventions, specifically targeting morphological omissions and syntactic additions, to substantively elevate students' academic writing proficiency and structural precision.